Bisnis Penginapan Berbasis Syariah Perspektif Hukum Ekonomi Islam - Hayatun Nufus (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2022)
Seven Dream Syariah Hotel Jember was the only lodging business that includes a sharia label on its business. Concerning Islamic law to avoid things that were violated, the researcher focuses on service transactions in the sharia-based lodging business that had been practised.Discussion in this study. How were service transactions in sharia-based lodging at Seven Dream Syariah Hotel Jember? How were service transactions in sharia-based lodging at Seven Dream Syariah Hotel Jember from the perspective of Islamic economic law? This research used qualitative methods. The data collected by the researcher includes primary and secondary data. While the source data was obtained through observation, interviews and documentation. Then the data were analyzed descriptively through data reduction, display and verification. Based on the results of the study, the presence of 'aqidain, mu'jir and musta'jir had reached puberty. The object of this transaction was the rental of guest rooms, meeting rooms and laundry services. In the pricing, tabaduli was due to a lack of information which results in ambiguity. The practice of this transaction was legal if the musta'jir did not object to paying the rental rate. If the mu'jir did not provide complete information and object, then the law was invalid.